Aboveground phytomass of green manure stubble crops on irrigated arable land in the Chui valley of Kyrgyzstan (Experimental biology, 2021)
The article discusses the prospects for the introduction of crop sideral crops - white mustard, white clover, spring barley, Rowan-leaved phacelia, oilseed radish on irrigated arable land in the Central part of the Chui valley of Kyrgyzstan after harvesting winter wheat, which corresponds to the basics of organic management of irrigated agriculture. When introducing stubble green manures, the organization of uninterrupted watering of plants during the growing season is of paramount importance. In the arid, hot summer climate of the Chui of the company Kirbi valley, the cultivation of crop siderates is accompanied by the use of regular irrigation using sprinklers.  This is the only way to ensure the cultivation of green manure and obtain a full-fledged green mass at the end of the growing season of the manure. The issues of accumulation of aboveground and root mass of sideral crops - white mustard, white clover, spring barley, Rowan-leaved phacelia, oilseed radish and their influence on increasing potato yield are studied. The procedure for increasing the aboveground mass of green manure is established: white mustard, white melilot, spring barley, rowan-leaved phacelia, oil radish in the variants of the experiment. The article considers the advantage of joint mineralization of hard - to-decompose forms of plant residues of the previous crop-winter wheat and green phytomass of crop siderates to replenish the organic matter of the soil and to obtain environmentally friendly crop production. The materials of the research work allow us to recommend crop sideral crops on the irrigated arable lands of the Central part of the Chui valley of the KYRGYZ Republic: white mustard, white clover, spring barley, Rowan-leaved phacelia, oilseed radish as green fertilizers.
Keywords: green manure, crop crops, plants, precursor, winter wheat, fertility, soil, irrigated arable land, yield, green fertilizer